(untitled) (Journal of the College of Basic Education, 2022)
The experiment was carried out with the aim of identifying the harmful effect of hydrogen peroxide (0,2,4)% and treating it with three increasing concentrations of humic fulvic acid (0,25,50) mg.L-1 and four concentrations of zinc (0,50,100,150) mg.L-1 in some of the major elements (nitrogen, phosphorus, potassium) and micro (zinc and iron) Randomized Complete Block Design with three replicates and 108 experimental units showed the following results: Hydrogen peroxide concentrations 4% have a negative effect on the values ​​of the studied traits The effect of both the humic fulvic acid and the zinc element had a positive effect on the content of the elements 3 - The role of the high concentrations of each of them to give an increase rates for all those qualities The triple interference between hydrogen peroxide concentrations 4% and spray with high concentration of acid and element was positive in reducing the impact of chemical stress. .